2007
DOI: 10.1017/s0022215107000576
|View full text |Cite
|
Sign up to set email alerts
|

Time trend analysis of otological procedures performed in England, 1989 to 2005

Abstract: The number of major otological procedures (other than endolymphatic sac surgery) was consistent over the period examined. The generally perceived reduction in the number of procedures performed by individual surgeons may be due to a dilutional effect. This can only support the need for subspecialisation, particularly regarding the training of junior surgeons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…They found that overall numbers were consistent; however, the increased provision of ENT services has led to a dilution effect and so they supported the need for subspecialization especially in training [23]. Our study has found a marginal increase in overall numbers, which may not be considered as clinically relevant with an increasing population.…”
Section: Discussionsupporting
confidence: 43%
See 2 more Smart Citations
“…They found that overall numbers were consistent; however, the increased provision of ENT services has led to a dilution effect and so they supported the need for subspecialization especially in training [23]. Our study has found a marginal increase in overall numbers, which may not be considered as clinically relevant with an increasing population.…”
Section: Discussionsupporting
confidence: 43%
“…Hari et al [23] performed a time trend analysis of otological procedures in England between 1989 and 2005 to investigate whether surgery for cholesteatoma is declining in developed countries. They found that overall numbers were consistent; however, the increased provision of ENT services has led to a dilution effect and so they supported the need for subspecialization especially in training [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mastoidectomy for the treatment of cholesteatoma is a common surgical procedure, constituting much of the surgical volume undertaken by otologists. The goal is to eradicate disease and to achieve a dry, stable ear, necessitating little aftercare.…”
Section: Introductionmentioning
confidence: 99%
“…An English study analyzed Government Hospital Episode Statistics (HES data) between 1985 and 2005, and reported no decline in the number of cholesteatoma operations in England over the 20-year study period [4]. However, these data were not adjusted for population increases.…”
Section: Introductionmentioning
confidence: 99%